1994
DOI: 10.1046/j.1365-2648.1994.20010110.x
|View full text |Cite
|
Sign up to set email alerts
|

Time for clients: temporal aspects of community psychiatric nursing

Abstract: Time is an integral element in all actions, organizations and relationships. Temporality has an effect on people's lives, and in turn people manipulate temporality as a means of imposing social order. From a semiotic perspective the amount of time spent on an action and the timing of its conveys messages about such things as importance and status. This holds equally true of organizations as well as individuals. This paper concentrates on a community psychiatric nursing department, its staff and clients. Sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 8 publications
1
14
0
3
Order By: Relevance
“…This includes the perception of a situation, relation with other people in a situation and how they experience their own position in the situation. As Gibson (1994) stated: ‘Time is an integral element in all actions, organizations and relationships’ (p. 110). The same applies from a semiotic perspective: ‘The amount of time spent on an action and the timing of it conveys messages about such things as importance and status’ (Gibson 1994, p. 110).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes the perception of a situation, relation with other people in a situation and how they experience their own position in the situation. As Gibson (1994) stated: ‘Time is an integral element in all actions, organizations and relationships’ (p. 110). The same applies from a semiotic perspective: ‘The amount of time spent on an action and the timing of it conveys messages about such things as importance and status’ (Gibson 1994, p. 110).…”
Section: Discussionmentioning
confidence: 99%
“…People experiencing waiting might also feel that they are neglected and are less worthy as persons. As Richman (1983) in Gibson (1994) summarized it:…”
Section: Discussionmentioning
confidence: 99%
“…The importance of ownership of the timetable is an issue that should not be overlooked, Gibson (1994) states that 'taking possession of time equates with taking control of the situation'. A patient who cannot express a temporal influence is on the one hand disorganised, yet on exerting a mastery he/she can encourage a psychiatric interpretation of illness.…”
Section: Patient Perspectivesmentioning
confidence: 99%
“…As Gibson (1994) points out, 'temporality has an effect on peoples lives, and in turn people manipulate temporality as a means of imposing social order'. In attempts to attain this type of time, the patient runs the risk of being perceived as uncooperative.…”
Section: Masterymentioning
confidence: 99%
“…Those that have present challenges, such as Jones (2001), in applying theory derivation to Adam's (1995) work and exploring temporality, timing and tempo in nursing practice. Other research (Gibson, 1994;Walsh, 1997), while not directly examining time, found that in the course of the Time & Society copyright © 2003 SAGE (London, Thousand Oaks, CA and New Delhi) VOL. 12 No.…”
Section: Introductionmentioning
confidence: 99%